Never Far From Nowhere - Andrea Levy (London, United Kingdom Headline Publishing Group, 1996)
NEVER FAR FROM NOWHERE is the story of two sisters, Olive and Vivien, born in London to Jamaican parents and brought up on a council estate. They go to the same grammar school, but while Vivien's life becomes a chaotic mix of friendships, youth clubs, skinhead violence, A-levels, discos and college, Olive, three years older and a skin shade darker, has a very different tale to tell...
Keywords: Relationships -- Relationships; Romance -- Romance